Anti-caking coke oven tube for preparing aluminum oxide layer based on surface roughness and manufacturing method thereof
The anti-coking furnace tube with a controlled Al2O3 oxide layer on a rough surface addresses coke deposition and oxidation issues, enhancing operational efficiency and durability by inhibiting coke deposition and oxidation.
Patent Information
- Application Number
- CN202411256624.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-27
AI Technical Summary
Existing ethylene cracking furnace tubes face issues with coke deposition and oxidation due to inadequate oxide layers, leading to reduced operational efficiency and equipment damage, with Cr2O3 layers being insufficient in preventing oxygen and carbon penetration and Al2O3 layers prone to peeling under temperature gradients.
An anti-coking furnace tube with a dense, evenly distributed Al2O3 oxide layer formed on a rough surface, controlled by specific surface roughness and alloy composition, including elements like Ni, Cr, Al, Si, Nb, Hf, Ti, Ta, Mn, and W, formed under low oxygen partial pressure conditions.
The Al2O3 oxide layer provides excellent adhesion and high-temperature stability, effectively inhibiting coke deposition and oxidation, extending the furnace tube's service life and reducing maintenance costs.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of cracking furnace tube manufacturing, and particularly relates to an anti-coking furnace tube with an aluminum oxide layer prepared based on surface roughness and a manufacturing method thereof. Background Art
[0002] The diameter of the ethylene cracking furnace tube is about 100 mm, the wall thickness is 10 mm, and the length is about 10 meters. It is expected to work for 5 years or more at a temperature of up to 1100°C. Therefore, they must have sufficient resistance to creep deformation (under their own weight), oxidation of their outer surface by combustion gases, and carbon and oxygen erosion on the inner surface. As the operating temperature of the ethylene cracking furnace increases, the furnace tube material is gradually upgraded: from HP, HK steel to AFA alloy, the composition is adjusted by microalloying, and the performance of the material is gradually improved. It is known that the operation cycle of the domestic ethylene cracking furnace is about 60 days, and it takes 3 to 4 days to stop the furnace for online coking after each operation cycle. On the one hand, the online coking of the cracking furnace consumes a lot of fuel, steam, electricity, and compressed air, which greatly reduces the effective production time of the cracking furnace. On the other hand, the coking process of the cracking furnace accelerates the damage of the equipment.
[0003] In-situ coating technology is based on the principle of catalytic coking. When the furnace tube is treated under specific atmosphere conditions, the Mn and Cr elements in the furnace tube are slowly oxidized to form an oxide protective layer on the surface of the furnace tube, and the Ni, Fe and other elements that are easy to cause catalytic coking are not easily oxidized in the furnace tube; the chromium spinel protective film is formed in situ on the inner surface of the furnace tube, and the Ni and Fe elements in the furnace tube material are shielded, and the anti-carburization performance of the furnace tube is effectively improved, thereby inhibiting the entire coking process of the cracking reaction and the catalytic coking reaction. The oxide film has the characteristics of dense grains, small grain size, good anti-coking performance and low stress between the substrate. The oxidation treatment is not limited by the shape of the sample and the cost is low.
[0004] Due to the low density of the Cr2O3 oxide layer, the function of preventing oxygen and carbon from entering is insufficient, resulting in internal oxidation in a high temperature atmosphere and thickening of the oxide film. In addition, the Cr2O3 oxide layer is likely to separate during repeated cycles of heating and cooling. Even if the Cr2O3 oxide layer does not separate, the Cr2O3 oxide layer does not have sufficient function to prevent oxygen and carbon from entering from the external atmosphere. Therefore, there is an unfavorable situation in which oxygen and carbon pass through the film and cause oxidation or carbonization inside the substrate.
[0005] During the long-term cycle coking process, the Al2O3 oxide film is easily affected by the temperature gradient and is prone to peeling and failure. In order to solve this problem, the Al2O3 oxide film with better stability can be generated on the surface, which is more helpful to inhibit coking. In addition to the addition of trace elements, the oxide layer also reduces the surface stress and has the characteristics of high density and stability, which can make it more difficult for oxygen and carbon to pass through, thereby improving the use value of the furnace tube. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes an anti-coking furnace tube with an aluminum oxide layer prepared based on surface roughness and a manufacturing method thereof. The aluminum oxide film on the surface of the anti-coking furnace tube manufactured by the present invention has good adhesion and high temperature stability, can effectively alleviate the coke deposition generated on the inner wall of the furnace tube during the cracking of petroleum hydrocarbons, and has good anti-oxidation performance.
[0007] The specific scheme of the present invention is as follows: An anti-coking furnace tube with an aluminum oxide layer prepared based on surface roughness comprises a substrate, a rough anti-coking furnace tube surface, and a dense and evenly distributed single Al2O3 oxide layer formed on the rough surface. The roughness Ra of the rough anti-coking furnace tube surface is between 0.40 and 0.063 μm.
[0008] Preferably, the chemical composition of the furnace tube material is, by weight percentage, C 0.1-0.5%, Cr 15-30%, Ni 20-45%, Al 2-5%, Si 0.3-2%, Nb 0.5-2%, Hf 0.1-0.3%, Ti ≤0.2%, Ta ≤0.2%, Mn ≤0.3%, W≤2%, Y ≤0.2%, and the rest is iron.
[0009] More preferably, the chemical composition of the furnace tube material is, by weight percentage, C 0.1-0.5%, Cr 15-30%, Ni20-45%, Al 2-4%, Si 0.3-2%, Nb 0.5-2%, Hf 0.1-0.3%, Ti 0.1-0.2%, Ta 0.1-0.2%, Mn 0.1-0.3%, W 0.1-2%, Y 0.01-0.1%, and the rest is iron.
[0010] Preferably, the thickness of the surface Al2O3 oxide layer is 0.3-2 μm.
[0011] The present invention also provides a method for manufacturing an anti-coking furnace tube by preparing an alumina layer based on surface roughness: preparing raw materials according to the chemical components required for the anti-coking furnace tube, smelting and then centrifugal casting to make a furnace tube, and then roughening the surface of the furnace tube by mechanical processing and other methods, and heat treating it in a low oxygen partial pressure atmosphere: the temperature is 850~1100℃, the time is 5~15h, and an alumina oxide layer will be directly formed on the surface. Among them, the low oxygen partial pressure atmosphere is a mixed atmosphere composed of reducing gas (H2), water vapor and inert gas (Ar), and the volume percentage of H2 in the low oxygen pressure atmosphere gas is 3%~5%, preferably 4%; the oxygen partial pressure can be accurately controlled to 1×10 by adjusting the water flow rate by a micro-injection pump. -15 ~1×10 -20atm, preferably 1.0x10 -17 atm: The volume percentage of H2O in the low oxygen pressure atmosphere gas is 0.2%~3%.
[0012] The technical principles and beneficial effects of the present invention are as follows: The anti-coking performance of austenitic stainless steel depends on the stability of the Al2O3 layer on its surface, and the stability of the Al2O3 layer is closely related to the oxidation process and alloy composition. When austenitic stainless steel is oxidized at high temperature in air, the Fe and Cr elements in the alloy will preferentially diffuse to the surface of the matrix to form oxides, hindering the external oxidation of Al; under low oxygen pressure conditions, the alloy will undergo selective oxidation. Among various oxides, Al and O have a stronger affinity, making Al2O3 easier to form. The Al content required to form a complete Al2O3 film needs to exceed a certain critical value, and the Cr element can reduce the minimum Al content required to form an Al2O3 oxide film. However, when the Al and Cr contents are too high, the matrix changes from a single FCC structure to a FCC+BCC dual-phase structure, which will promote the formation of the σ phase, resulting in a decrease in the high-temperature creep resistance of the alloy. Therefore, it is necessary to control Cr 15~30% and A1 2~5%.
[0013] Increasing the Ni and Mn content can improve the stability of austenite. However, high Mn content will weaken the effect of the surface oxide film, reduce the oxidation resistance of the heat-resistant steel, and reduce the corrosion resistance of the heat-resistant steel. Therefore, the Mn content is controlled below 0.3%.
[0014] Appropriate amounts of Si, Ti, Ta and Nb are added to improve the oxidation resistance and creep resistance of the alloy. Si and Hf can improve the thermal stability of the oxide film and fill the gap between the oxide film and the substrate, thereby playing a "pinning" role. Appropriate amounts of Si can improve the adhesion of the oxide film, reduce the carburization rate, and promote the external oxidation of Al. Appropriate amounts of Hf play an important role in refining grains and improving strength and toughness. It preferentially concentrates near the grain boundary and interacts with the impurity elements at the interface to purify the grain boundary. Adding an appropriate amount of Nb to the alloy can form fine and dispersed NbC particles, which helps to improve the creep performance, while excessive Nb content will lead to a decrease in the creep resistance of the alloy, which is mainly due to the formation of undissolved and coarsened Nb particles during the solid solution process, which hinders the precipitation of nano-scale MC. In addition, Nb can promote the growth of B2-NiAl phase and reduce oxygen solubility, which is conducive to the formation of Al2O3 protective film. The addition of W can play a role in solid solution strengthening and greatly enhance the creep performance of the alloy.
[0015] The furnace tube surface has a certain degree of roughness, which can promote the diffusion of elements in a low-oxygen atmosphere. Compared with the O element, metal elements are more likely to diffuse outward. A lower roughness will cause the diffusion of Cr and thus prevent the generation of Al2O3. Although a higher roughness is more conducive to the formation of Al2O3, it is prone to peeling of the oxide film during a long period of cyclic decoking, resulting in failure.
[0016] The outer surface of the furnace tube prepared by the present invention generates a complete Al2O3 oxide layer, and the oxide layer has good adhesion on the substrate surface and good high temperature stability, and can effectively inhibit the deposition of coke on the furnace tube surface. In the test process of cyclic coking, the performance is excellent, and the addition of trace elements such as Hf and Y, as well as the control of surface roughness, reduces the stress in the oxide film, further improves the adhesion of the oxide film, and increases its service life. In addition, the manufacturing method of the present invention has the same effect on high-Ni austenitic alloys and low-Ni austenitic alloys, and can effectively save costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 (a) The surface laser confocal microscope optical image and (b) 3D morphology image of the furnace tube surface before pre-oxidation heat treatment in Example 1, and (c) The surface laser confocal microscope optical image and (d) 3D morphology image of Comparative Example 1; Figure 2 (a) microscopic morphology and (b) partial magnified image of the furnace tube surface after pre-oxidation heat treatment in Example 1; Figure 3 (a) backscattered electron image and (b) component surface distribution image of the cross section of the furnace tube after pre-oxidation heat treatment in Example 1; Figure 4 The surface of the furnace tube before pre-oxidation heat treatment in Comparative Example 1 is (a) backscattered electron image, (b) NbC component energy spectrum image, (c) B2-NiAl component energy spectrum image, (d) FCC component energy spectrum image, and (e) HfC component energy spectrum image; Figure 5 (a) surface microscopic morphology and (b) cross-sectional backscattered electron image of the furnace tube after pre-oxidation heat treatment in Comparative Example 1; Figure 6 For the furnace tube (a) surface microscopic morphology and (b) cross-sectional backscattered electron image after pre-oxidation heat treatment in Comparative Example 2; Figure 7 (a) Microscopic morphology and (b) partial magnified image of the furnace tube surface after pre-oxidation heat treatment in Comparative Example 3; Figure 8 (a) microscopic morphology, (b) Al2O3 component energy spectrum, and (c) Cr2O3 component energy spectrum of the furnace tube surface after pre-oxidation heat treatment in Comparative Example 4; Fig. 9(a) Microscopic morphology and (b) coke component spectrum of the surface of Comparative Example 5 after reaction in a petroleum cracking atmosphere at 850°C for 15 hours; Fig.10 (a) surface microscopic morphology and (b) cross-sectional backscattered electron image of the furnace tube after pre-oxidation heat treatment in Example 2; Fig.11 (a) surface microscopic morphology and (b) cross-sectional backscattered electron image of the furnace tube after pre-oxidation heat treatment in Example 3; Fig.12 The backscattered electron images of the cross-section of 4, 4.2, 4.5Al furnace tubes after pre-oxidation heat treatment in Example 4; Fig.13 It is the creep time (h)-creep deformation (mm) diagram of 45Ni-25Cr-xAl (x=4, 4.2, 4.5)-1Nb-0.2Mn-0.3Si-0.15Ti-0.15Ta-0.06Y-0.45C-1W-Fe residue at 1000℃ and 30MPa load; Fig.14 A comparison chart of the weight gain per unit area of the HP40 furnace tube, HK40 furnace tube, Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Comparative Example 6 furnace tubes reacted in a petroleum cracking atmosphere at 850°C for 15 hours; Fig.15 The cross-sectional backscattered electron images of the furnace tubes of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 6 were exposed to an 850°C petroleum cracking atmosphere for 10 hours and then exposed to a high-temperature water vapor environment at 850°C for 2 hours for decoking. This cycle of decoking was repeated 5 times to obtain the cross-sectional backscattered electron images. DETAILED DESCRIPTION
[0018] The present invention is further described below by combining specific embodiments. The embodiments described below are only used to explain the present invention, but not to limit the protection scope of the present invention. Example 1
[0019] The chemical composition of the furnace tube alloy is, by weight percentage, 4% Al, 20% Cr, 25% Ni, 0.3% C, 1% Si, 1.5% Nb, 0.15% Ti, 0.1% Ta, 0.15% Mn, 0.1% W, 0.06% Y and 0.2% Hf, with Fe as the balance.
[0020] The manufacturing method of the anti-coking furnace tube of the aluminum oxide layer prepared based on the surface roughness, the specific steps are as follows: S1, putting the alloy raw materials according to the above weight percentage into a vacuum melting furnace for melting, the purity of all metal raw materials is 99.99%, the addition of C element is introduced through the intermediate alloy Fe5C, the melting current is 120A, the front and back sides of the alloy are melted twice, each melting time is 4 minutes, to avoid alloy component segregation; S2, the smelted alloy is cast into a seamless furnace tube with a diameter of 8 mm and a wall thickness of 1.2 mm by centrifugal casting, the inner surface of the furnace tube is machined, and 800-mesh sandpaper is selected for grinding to make its roughness Ra value = 0.18 μm; S3, heat treatment is performed on the furnace tube treated in step S2 in a low oxygen partial pressure atmosphere, the oxidation temperature is 1000°C, the oxidation time is 5h, the oxidation atmosphere is 4% H2+Ar mixed gas, the mixed gas flow rate is 30L / h, the volume percentage of H2O in the low oxygen pressure atmosphere gas is 2%, and the oxygen partial pressure is 1.0×10 -17 atm; S4, coking experiment: The coking experiment was carried out in a cracking atmosphere with industrial naphtha as the cracking raw material (naphtha distillation range is 80-100), and the cracking time was 15h.
[0021] The roughness of the furnace tube surface after machining was observed and analyzed by laser confocal microscopy, as shown in Figure 1. The surface, cross-sectional morphology and composition of the furnace tube after pre-oxidation heat treatment were observed and analyzed by scanning electron microscopy (SEM) and energy dispersive spectrometer (EDS), as shown in Figure 1. Figure 2 and Figure 3 As shown, the thickness of the Al2O3 oxide film is about 0.35 μm, and the coking mass gain in a short period of time is as follows Fig.14 As shown, after the cyclic coking test, the cross-sectional backscattering diagram is as follows Fig.15 As shown, there is no clear carburized layer on the cross section, and all exhibit excellent and stable performance characteristics. Comparative Example 1
[0022] Compared with Example 1, the surface is machined in step S2, pre-grinded with 150 mesh, 400 mesh, 1000 mesh and 2000 mesh sandpaper in sequence, and then polished with Al2O3 polishing liquid. Chemical polishing and electrolytic polishing can also be used to make its roughness Ra=0.02μm. The rest of the operations are the same as in Example 1.
[0023] The surface morphology and composition of the furnace tube before pre-oxidation heat treatment were observed and analyzed by scanning electron microscopy (SEM) and energy dispersive spectrometer (EDS). Figure 4 As shown in the figure, the morphology of the furnace tube surface and cross section before and after pre-oxidation treatment is as follows: Figure 5 As shown in Figure 2, the coking mass gain in a short period of time is as follows: Fig.14 shown.
[0024] In comparative example 1, the surface is smooth and a composite oxide film is formed. The outer surface is chromium oxide with a thickness of about 5 μm and the inner surface is aluminum oxide with a depth of about 6 μm. Compared with HK40 and HP40, it has a significant effect, but it is far less effective than the anti-coking gain of aluminum oxide film. Moreover, after the cyclic coking test, the cross-sectional backscattering diagram of the outer Cr and inner Al film is as follows: Fig.15 As shown in the figure, the Cr film can be clearly observed to fall off. Therefore, it can be seen that the aluminum oxide film is better than the chromium oxide film. Comparative Example 2
[0025] Compared with Example 1, in step S2, the surface is machined and polished with 150-mesh sandpaper to a roughness of Ra=0.72 μm. The remaining operations are the same as in Example 1.
[0026] In Comparative Example 2, the morphology of the furnace tube surface and cross section before and after the pre-oxidation treatment and the coking mass gain in a short period of time are shown as follows: Figure 6 Shown and Fig.14 As shown, there is little difference from Example 1. However, after the cyclic coking test, the cross-sectional backscattering diagram is as follows Fig.15 As shown in the figure, serious carburization can be seen. The reason is that the greater roughness makes it easy for the Al2O3 layer on the surface to peel off, and the rough surface that still exists after peeling promotes the diffusion of C into the surface, forming a thicker diffusion layer. Comparative Example 3
[0027] Compared with Example 1, the oxidation temperature during the pre-oxidation treatment in step S3 is 1100°C, and the remaining operations are the same as those in Example 1. The surface of the furnace tube after the pre-oxidation heat treatment is analyzed by scanning electron microscopy and energy dispersive spectrometer. The SEM image is as follows: Figure 7 As shown in Figure 2, the coking mass gain in a short period of time is as follows: Fig.14 shown.
[0028] from Figure 7 It can be seen that although an aluminum oxide film was generated at high temperature, large-scale peeling occurred, resulting in an exposed substrate, thus losing the meaning of pre-oxidation. Comparative Example 4
[0029] Compared with Example 1, when the pre-oxidation treatment in step S3 is performed, the oxidation temperature is 650°C and the oxidation time is 15 hours. The remaining operations are the same as those in Example 1. The surface of the furnace tube after the pre-oxidation heat treatment is analyzed by scanning electron microscopy and energy dispersive spectrometer. The SEM image is as follows: Figure 8 As shown in Figure 2, the coking mass gain in a short period of time is as follows: Fig.14 shown.
[0030] from Figure 8It can be seen that the surface oxide film is composed of both chromium oxide and aluminum oxide. Considering the anti-coking gain, it is not as good as a single aluminum oxide film. Moreover, the thermal expansion coefficients of the two different oxide films are different, and cracking is likely to occur during long-term use, causing the oxide film to fail. Comparative Example 5
[0031] Compared with Example 1, the pre-oxidation treatment in step S3 is not performed, and the remaining operations are the same as those in Example 1. The surface of the furnace tube after short-time coking is analyzed by scanning electron microscopy and energy dispersive spectrometer. The SEM image is as follows: Fig. 9 As shown in Figure 2, the coking mass gain in a short period of time is as follows: Fig.14 As shown. Fig. 9 It can be seen that the surface is covered with carbon, which is not conducive to anti-coking at all. Comparative Example 6
[0032] Compared with Example 1, the chemical composition of the anti-coking furnace tube is changed to: 4% Al, 20% Cr, 35% Ni, 0.3% C, 1% Si, 1.5% Nb, 0.15% Mn and 0.06% Y, with Fe as the balance. The rest of the operation is the same as Example 1. The coking mass gain in a short time is as follows Fig.14 As shown, after the cyclic coking test, the cross-sectional backscattering diagram is as follows Fig.15 As shown. The anti-coking performance is excellent in a short time, but after a long cycle coking test, matrix carburization occurs. The lack of Hf and Ta elements greatly reduces the adhesion of the oxide film, resulting in the peeling of the oxide film during long-term use, causing C to enter the matrix, resulting in extremely high oxidation gain. Example 2
[0033] Compared with Example 1, the chemical composition of the anti-coking furnace tube is changed to: 4% Al, 20% Cr, 45% Ni, 0.3% C, 1% Si, 1.5% Nb, 0.15% Ti, 0.1% Ta, 0.15% Mn, 0.06% Y, 0.1% W and 0.2% Hf, with Fe as the balance. The rest of the operation is the same as in Example 1. The surface and cross section of the furnace tube after the pre-oxidation heat treatment are analyzed by scanning electron microscopy and energy spectrometer, and the SEM images are as follows Fig.10 As shown, the thickness of the aluminum oxide film is about 0.9 μm. The coking mass gain in a short time and the cross-sectional backscattering diagram after the cyclic coking test are shown in Fig.14 and Fig.15 As shown, the performance of high-Ni alloy at high temperature should be superior to that of low-Ni alloy. The performance difference needs to be manifested over a longer period of time. The results are similar to those of Example 1, and the overall performance is excellent. Example 3
[0034] Compared with Example 1, in step S2, the surface is machined and polished with 2000 mesh to a roughness Ra of 0.09 μm. The remaining operations are the same as those in Example 1. The surface and cross section of the furnace tube after the pre-oxidation heat treatment are analyzed by scanning electron microscopy and energy dispersive spectrometer. The SEM images are shown in FIG. Fig.11 As shown, the thickness of the aluminum oxide film is about 0.85 μm. The coking mass gain in a short time and the cross-sectional backscattering diagram after the cyclic coking test are shown in Fig.14 and Fig.15 As shown, the results are similar to those of Example 1, and a wider roughness range is beneficial to processing flexibility. Example 4
[0035] The chemical composition of the anti-coking furnace tube is: 45% Ni, 25% Cr, x% Al (x = 4, 4.2, 4.5), 1% Nb, 0.2% Mn, 0.3% Si, 0.15% Ti, 0.15% Ta, 0.45% C, 0.06% Y, 1% W, and Fe is the balance. The pre-oxidation operation is the same as in Example 1. The cross-section of the 4, 4.2, and 4.5 Al furnace tubes after pre-oxidation heat treatment is analyzed by scanning electron microscopy and energy spectrometer. The SEM images are shown in FIG. Fig.12 As shown in Figure 2, with the addition of Al content, it is beneficial to form a thicker Al2O3 oxide film, which is obvious, but excessive Al content will lead to the formation of BCC phase, so it is necessary to select an appropriate Al content. The high temperature creep test was carried out at 1000℃ and 30MPa load, and the creep time (h)-deformation (mm) diagram is shown in Figure 2. Fig.13 As shown, its creep performance is good.
[0036] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An anti-coking furnace tube, characterized in that: The anti-coking furnace tube comprises a substrate, a rough anti-coking furnace tube surface, and an Al2O3 oxide layer formed on the rough surface; the roughness Ra of the rough anti-coking furnace tube surface is 0.40-0.063 μm; the chemical composition of the anti-coking furnace tube is C 0.1-0.5%, Cr 15-30%, Ni 20-45%, A1 2-5%, Si 0.3-2%, Nb 0.5-2%, Hf 0.1-0.3%, Ti ≤0.2%, Ta ≤0.2%, Mn ≤0.3%, W ≤2%, Y ≤0.2%, and the rest is iron.
2. The anti-coking furnace tube according to claim 1, characterized in that: The chemical composition of the anti-coking furnace tube is, by weight percentage, C 0.1-0.5%, Cr 15-30%, Ni 20-45%, Al 2-4%, Si 0.3-2%, Nb 0.5-2%, Hf 0.1-0.3%, Ti 0.1-0.2%, Ta 0.1-0.2%, Mn 0.1-0.3%, W 0.1-2%, Y 0.01-0.1%, and the rest is iron.
3. The anti-coking furnace tube according to claim 1, characterized in that: The thickness of the Al2O3 oxide layer is 0.3-2 μm.
4. The method for manufacturing the anti-coking tube according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: preparing raw materials according to the chemical components required for the anti-coking furnace tube, making the furnace tube by centrifugal casting after smelting, roughening the surface of the furnace tube, performing heat treatment in a low oxygen partial pressure atmosphere, and directly forming an Al2O3 oxide layer on the surface.
5. The method for manufacturing an anti-coking tube according to claim 4, characterized in that: The low oxygen partial pressure atmosphere consists of H 2、 The low oxygen pressure atmosphere is composed of water vapor and Ar, wherein the volume percentage of H2 in the low oxygen pressure atmosphere gas is 3-5%; the volume percentage of H2O in the low oxygen pressure atmosphere gas is 0.2-3%.
6. The method for manufacturing an anti-coking tube according to claim 4, characterized in that: The oxygen partial pressure is 1×10 -15 ~1×10 -20 atm, and the water flow rate was controlled by adjusting the micro-injection pump.
7. The method for manufacturing an anti-coking tube according to claim 4, characterized in that: The heat treatment temperature is 850-1100° C., and the heat treatment time is 5-15 hours.